2007
DOI: 10.1007/s11068-007-9014-3
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic destabilization by neuronal Nogo-A

Abstract: Formation and maintenance of a neuronal network is based on a balance between plasticity and stability of synaptic connections. Several molecules have been found to regulate the maintenance of excitatory synapses but nothing is known about the molecular mechanisms involved in synaptic stabilization versus disassembly at inhibitory synapses. Here, we demonstrate that Nogo-A, which is well known to be present in myelin and inhibit growth in the adult CNS, is present in inhibitory presynaptic terminals in cerebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 60 publications
4
59
0
Order By: Relevance
“…Indeed, 2D2 3 TIGIT 2/2 mice showed atypical signs of neurologic dysfunction as early as 28 d after birth (Fig. 3B), and with advancing age all 2D2 3 TIGIT 2/2 mice displayed dyskinesia, ataxia, and a clasping phenotype (9). Some of the 2D2 mice also showed these atypical symptoms.…”
Section: Tigitmentioning
confidence: 90%
“…Indeed, 2D2 3 TIGIT 2/2 mice showed atypical signs of neurologic dysfunction as early as 28 d after birth (Fig. 3B), and with advancing age all 2D2 3 TIGIT 2/2 mice displayed dyskinesia, ataxia, and a clasping phenotype (9). Some of the 2D2 mice also showed these atypical symptoms.…”
Section: Tigitmentioning
confidence: 90%
“…This probably toxic overexpression is in line with earlier similar observations. 18,30 The situation in the retina therefore also differs from a model of ALS, where the ablation of the Nogo-A/B gene accelerated the degeneration of ventral motor neuron axons, 15 whereas the systemic absence of Nogo-A slowed the disease, and Nogo-A overexpression in muscle enhanced neuromuscular endplate degeneration. 30 Recent studies showed that the neutralization of Lingo or NgR1, 2 receptor components for Nogo-A, promoted RGC survival after optic nerve transection.…”
Section: Discussionmentioning
confidence: 99%
“…15 Only few and contradictory observations are available on such a role of Nogo (reticulon 4 (RTN4)) or other RTN proteins, and they rely mostly on in vitro or overexpression experiments. 15,[17][18][19][20][21] We therefore investigated axonal regeneration and survival of RGCs after optic nerve crush in mice with systemic Nogo-A deletion (KO) or neuron-specific knock down using adeno-associated virus vector of serotype 2 (AAV2) that selectively infect RGCs in the retina. For the first time, our work demonstrates that the exogenous increase of neuronal Nogo-A driven by AAV2.Nogo-A, but not the endogenous upregulation of neuronal Nogo-A because of axonal damage enhanced RGC cell loss.…”
mentioning
confidence: 99%
“…In ngr1 (McGee et al, 2005) and in pirB knock-out mice (Syken et al, 2006), ocular dominance plasticity continues after the end of the critical period, suggesting that NgR1 and PirB signaling contribute to stabilizing the neural circuitry and to temporally limit experiencedependent plasticity. In the mouse cerebellum, overexpression of Nogo-A leads to an age-dependent destabilization and loss of synapses of Purkinje cells (Aloy et al, 2006). Furthermore, NgR1 signaling has been shown to regulate activity-dependent synaptic strength in hippocampal CA1 neurons (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%